Source, oil charging history and filling pathways of the Ordovician carbonate reservoir in the Halahatang Oilfield, Tarim Basin, NW China. (May 2016) - Xiao, Zhongyao; Li, Meijun; Huang, Shaoying; Wang, Tieguan; Zhang, Baoshou; Fang, Ronghui; Zhang, Ke; Ni, Zhiyong; Zhao, Qing; Wang, Daowei
Abstract: The Ordovician reservoir in the Halahatang Depression is one of the most commercially prolific oil reservoirs in the Tabei Uplift of the Tarim Basin, NW China. For this study, a total of 94 oil samples were collected from 88 exploration/production wells in this oilfield. All of the oils possess similar organic molecular compositions and belong to the same oil population. Oil-to-source correlation results indicate that oil accumulations discovered in Halahatang Oilfield were derived from the Upper Ordovician source rocks. The homogenization temperatures of fluid inclusion in the Ordovician reservoir in the Halahatang Oilfield range from 90 °C to 100 °C and from 140 °C to 160 °C. The bimodal distribution pattern shown in a histogram of the homogenization temperatures indicates that the Ordovician oil reservoir in the Halahatang Oilfield has been charged twice. Coupling this information with the reconstructed burial and geothermal histories by 1-D basin modeling, the homogenization temperatures can be related to the relative geological ages of 419 Ma to 410 Ma and 16 Ma to 8 Ma, namely, the Middle to Late Silurian and the Middle Miocene respectively, representing the two phases of oil charging and entrapment. The oil migration orientation and charging pathways can be traced using molecular indicators, such as Ts/(Ts + Tm) and TMNr parameters. The overall oil migration orientation in the oilfield is generally from south to north. Therefore, the source kitchen for the Halahatang Oilfield is predicted to be to the south side of the depression. The southern part of the Halahatang Depression, along the oil charging pathways, is identified as the most promising region for oil exploration. Highlights: Oil population in the Halahatang Oilfield is classified. Timing and phases of Ordovician oil entrapment are determined. Oil migration orientation is investigated.